Pengaruh literasi keuangan dan demografi terhadap perencanaan pensiun pada individu pekerja di Surabaya - Wibisono, Audi; Anastasia, Njo (Journal of Economics Research and Policy Studies, 2024)
Financial literacy plays a crucial role in preparing retirement planning. Without a good understanding of financial management, individuals will face financial challenges when retirement. This study examines the effect of financial literacy and demographics on individual retirement planning in Surabaya. This type of research is a comparative analysis with a sample of individuals already working and domiciled in Surabaya, selected using a purposive sampling technique and obtained 141 respondents. The data collection technique used a questionnaire distributed online via Google Forms on WhatsApp and Line media. The data analysis technique used was a Chi-square and one-way ANOVA test. The study results showed that financial literacy is essential in saving decisions but does not affect the savings chosen. Demographic factors such as age, education, income, gender, and marital status significantly influence saving decisions with a sign level, while only gender and marital status affect the choice of savings categories. This study implies that pension policies and programs should be designed by considering demographic characteristics, such as education level and income, to be more effective in encouraging retirement-saving behavior.